PENGEMBANGAN RUANG INKUBASI SENI MELALUI LOKAKARYA KURATORIAL DAN PENULISAN SENI SEBAGAI UPAYA PENGUATAN EKOSISTEM SENI KOTA SOLO - Varatisha Anjani Abdullah; Dessy Rachma Waryanti (PUAN INDONESIA, 2026)
The curatorial and art writing workshop aimed to expand access for the residents of Solo—particularly young people—to contemporary art spaces. As the city of Solo continues to evolve and is no longer defined solely as a classical cultural city, it faces the reality of having a limited number of adequate, affordable, and inclusively accessible art presentation spaces for all segments of society. The program was implemented in stages using a collective governance approach, emphasizing an equal-participation and collaboration-based working system grounded in a spirit of kinship, participation, collaboration, and a long-term orientation toward sustainable ecosystem development. This approach involved artists, audiences, partners, and the broader community. The event was carried out smoothly with a total of 15 participants. The participants came from various regions, including Salatiga, Yogyakarta, and Solo itself, and were predominantly young people. The outcome of this activity was the establishment of an art space called Tafata Art Hub, designed as a venue for diverse artistic activities, particularly in the city of Solo.